Second generation of cata-annulated azaacene bisimides: towards electron accepting materials - Hippchen, Nikolai; Heinzel, Elena; Zhang, Cathy K.; Jäger, Patrick; Elter, Maximilian; Ludwig, Philipp; Rominger, Frank; Freudenberg, Jan; Cao, Dennis D.; Bunz, Uwe H. F. (ChemPlusChem, 2023)
We present the 2nd generation of cata-annulated azaacene bisimides with increased electron affinities (up to -4.38 eV) compared to their consaguine conventional azaacenes. These compounds were synthesized via Buchwald-Hartwig coupling followed by oxidation with MnO2. Crystal structure engineering through variation of the bisimide substituents furnished crystalline derivatives suitable for proof of concept organic field effect transistors with electron mobilities up to 2.2 x10-4 cm2(Vs)‑1. Moreover, we were able to characterize the charge carrying species, the radical anion, using electron paramagnetic resonance and absorption measurements.